2017
DOI: 10.14744/anatoljcardiol.2016.7222
|View full text |Cite
|
Sign up to set email alerts
|

NKX2-5 molecular screening and assessment of variant rate and risk factors of secundum atrial septal defect in a Moroccan population

Abstract: Objective:Secundum atrial septal defect (ASDII) has multifactorial etiology that is combination of environmental (e.g., mother’s exposure to toxicity, ethnicity) and genetic causes. Aim of the present study was to screen a Moroccan population with ASDII for NKX2-5 variants and to assess risk factors that may contribute to emergence of the disorder.Methods:Thirty-two non-syndromic ASDII patients were screened for NKX2-5 variants using direct sequencing of polymerase chain reaction-amplified coding regions. Risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In this study, it was frequently found that as much as 85.6% of research subjects. This result is the most significant number after research in the population in China, 80.18%, but it was found lower in Germany (59.4%) and Morocco (56.2%) [7,8,11,12].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In this study, it was frequently found that as much as 85.6% of research subjects. This result is the most significant number after research in the population in China, 80.18%, but it was found lower in Germany (59.4%) and Morocco (56.2%) [7,8,11,12].…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have reported a genetic variant of NKX2-5 linked to the development of atrial septal defect [6,7]. The frequency of gene variant of NKX2-5 in ASD patients with familial history could reach up to 8% and only 1-4% in sporadic cases [8]. Familial genetic variants can be detected earlier, so the management is possible to be carried out before complications appear.…”
Section: Introductionmentioning
confidence: 99%
“…Three synonymous variations in NKX2-5 are significantly associated with cases compared to controls in our cohort. Earlier reports also suggest the implication of synonymous variants of NKX2-5 in disease pathogenesis (Belvís et al, 2009;Boldt et al, 2010;Posch et al, 2008;El Bouchikhi et al, 2017). However, studies confirming their potential downstream effects are not well documented.…”
Section: Discussionmentioning
confidence: 99%
“…There are many inconsistencies in the published study results regarding the role of rs2277923 in the NKX2-5 gene, including Iranian [ 14 ] Asian [ 15 ] Moroccan [ 16 ], and Caucasian population [ 17 ]; hence, it is needed to analyze all the available published literature that provide us the most definite results for the role of rs2277923 polymorphism in congenital heart diseases.…”
Section: Introductionmentioning
confidence: 99%